2022
DOI: 10.3390/rs15010111
|View full text |Cite
|
Sign up to set email alerts
|

Driver of the Positive Ionospheric Storm over the South American Sector during 4 November 2021 Geomagnetic Storm

Abstract: During geomagnetic storms, ionospheric storms can be driven by several mechanisms. Observations performed using ground- and space-based instruments were used to reveal the driver of the positive ionospheric storm over the South American sector during the 4 November 2021 geomagnetic storm. The positive storm appeared from 10:30 UT to 18:00 UT and covered the region from 40°S to 20°N. The maximum magnitudes of TEC (Total Electron Content) enhancement and relative TEC enhancement were about 20 TECU and 100%, resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 39 publications
4
9
0
Order By: Relevance
“…The magnitude of storm-time TEC enhancements is about 40%-60% in the EIA crests region and 20%-30% in the equatorial trough region. This positive ionospheric storm was also reported by Zhai et al (2022) using 2-D ground-based GNSS TEC and 1-D in situ measurements, which are consistent with our 3-D ionospheric imaging results.…”
Section: Results and Validationsupporting
confidence: 92%
See 2 more Smart Citations
“…The magnitude of storm-time TEC enhancements is about 40%-60% in the EIA crests region and 20%-30% in the equatorial trough region. This positive ionospheric storm was also reported by Zhai et al (2022) using 2-D ground-based GNSS TEC and 1-D in situ measurements, which are consistent with our 3-D ionospheric imaging results.…”
Section: Results and Validationsupporting
confidence: 92%
“…These results suggest that an enhanced eastward electric field component and upward E × B drifts, resulting from the penetration electric field that led to the ionosphere being lifted to a higher altitude with a lower recombination rate, could be one of key drivers causing this positive ionospheric storm. The data assimilation results align well with observations made by Zhai et al (2022), who used the ionosonde and ICON drift measurements to prove the aforementioned electrodynamic effect. Moreover, Zhai et al (2022) reported a ∼50% enhancement in O/N 2 in the equatorial and low-latitude regions of South America, as observed by the Global-scale Observations of the Limb and Disk (GOLD) satellite.…”
Section: Results and Validationsupporting
confidence: 86%
See 1 more Smart Citation
“…ionosphere responses to geomagnetic disturbances (Aa et al, 2022;C. S. Lin et al, 2022;Liou et al, 2005;Lu et al, 2012;Meier et al, 2005;Verkhoglyadova et al, 2017;Zhai, Cai, et al, 2023;Zhai, Tang, et al, 2023; since it reflects the production and loss of the ionospheric F-region plasma (Rishbeth, 1998). Additionally, O and N 2 are two of the major components of the thermosphere, influencing the total mass density of the thermosphere, which is important for monitoring and predicting the drag force of low-Earth-orbiting satellites (Dietrich et al, 2022).…”
mentioning
confidence: 99%
“…During the transportation and corotation process, the formed disturbance can also be altered by background winds (Cai, Burns, Wang, Qian, Solomon, et al., 2021). The thermospheric composition disturbance make contributions to the corresponding ionosphere plasma density variations to result in positive or negative ionospheric storm effect (density enhancement or depletion), especially in the daytime mid‐latitude (Fuller‐Rowell et al., 1994; Rishbeth, 1998; Zhai et al., 2022). Furthermore, the equatorward or poleward wind during storm can transport the plasma along the magnetic field line to impact the plasma density variations (J. Liu, Wang, Burns, Yue, et al., 2016), as well as the E × B drifts influenced by penetration electric field (Lu et al., 2012, 2013; Wang et al., 2010).…”
Section: Introductionmentioning
confidence: 99%